ISLAM DAN MORAL BANGSA - As’ad, Mahrus (JURNAL NIZHAM, 2014)
The article is to explain the function of Islam as the concrete gudance and its relationship with the morality of the nation. Through the descriptive-analitical approache, it can be stated that the function of Islam asÂ the concrete gudance of the nation lies in a complext relationship with the whole cultural elements of the nation in one side and the system of values and norms operating concretely in the societies in other side. How completely this religion provides its moral system as the cutural capital of the nation if it lies in a small portion of the arena of the culture of the nation, it will become a mere formal atribute which will not give a significant influence on the formation of the moral attitude of the nation. The absence of the congruence relationship between the sacreed mission of the religion and the moral life of the society can be understood that the existence of the religion is antropologically not sufficient to become âthe policeâ having ability to control the moral attitude of the societies because of its marginal positionÂ in the configuration of our culture. Hence, it is not fair to blame all of the anomalies of the society on the religion, because there are still many other determinat variables exceptÂ the religion, including the governmentÂ apparatusâ example. The appearance of the disobedience of some parts of societiesÂ to the social values and norms does not always denote the moral wickedness of the nation. However, it means a social criticism. the disobedience to the social values and norms will jeopardize the social order if it is carried out for the sake of indivial and communal pleausre. The operation of Islamic stipulations in a concrete manner must be supported by all of the institutions existing in the society, including the family, education institution, and the government.Â Keywords: Culture, operation, morality,Â community, discipline.